Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function - Davies, Gail; Lam, Max; Harris, Sarah E.; Trampush, Joey W.; Luciano, Michelle; Hill, W. David; Hagenaars, Saskia P.; Ritchie, Stuart J.; Marioni, Riccardo E.; Fawns-Ritchie, Chloe; Liewald, David C. M.; Okely, Judith A.; et al. (Nature communications, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10-8) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.